Motherscholaring: a collective poetic autoethnographic inquiry. Issue 4 (21st April 2023) - Howard, Joy; Nash, Kindel; Thompson, Candace
Abstract: Motherscholaring is an essential mode of intellectual and spiritual travel, a type of soulwork, epistemologically rooted in love, occuring at the intersections of personal and professional theories, research, and practices that move toward justice. In this conceptual paper, we creatively and collectively explore meanings of motherscholaring found through poetic inquiry. The aim of this paper is twofold: (a) to add to emergent literature on the concept of motherscholaring and (b) to offer methodological contributions to the developing field of poetic inquiry by demonstrating and discussing the process and forms of poetic inquiry that have been useful in our communal project.